PARTISIPASI MASYARAKAT PADA KEGIATAN MUSRENBANG DESA DI DESA BALAI SEPUAK KECAMATAN BELITANG HULU KABUPATEN SEKADAU - Ignasius Chrismassiswanto Taena E.211111 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The writing of this article aims to determine the preformance community participation in village activities musrembang village hall appoint sub Belitang Hulu. This study included in the descriptive study with a qualitative analysis focusing on variable; Factor Age, Factor Gender, Factor Education, income and income, duration of stay. Results of research in the field shows that community participation in village activities musrenbang still very low because there are many rural communities that lack appoint Hall to attend every activity musrembang village. This is due to several factors that inhibit community participation asnamely, age, gender, education, occupation and income, and length of stay. Number of people who do not follow musrenbangdes relatively young because they do not have to participate but only the old folks who have to go and still a lot of women do not attend musrenbangdes. Education is still low makes no understandedmusrenbang the benefits of society and the economy is still low because most of them farm jobs, lack of any sense of belonging to the local community especially people who were the original inhabitants of the area. It is expected that the future further increase participation in every activity musrenbang villages, and each village hall appoint officials more often socialize the village to the community planning forums. Keywords: FactorAge, Factor Gender, Factor Education, workandIncome, length ofstay